Solve for the x-variable: 10x - 3 = 9x
*Rewrite the equation as: 9x = 10x - 3
First: combine "like" terms on one side (left)--- combine the coefficients with the x-variable > subtract "10x" from both sides (when you move a term to the opposite side, always use the opposite sign)...
9x - 10x = 10x - 10x - 3
9x - 10x = - 3
Sec: combine the terms with the x-variable...
- x = - 3
Third: rule > the x-variable has to be positive ---change the signs on both sides...
x = 3
2007-02-09 05:22:06
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
10x-9x=3 so x=3
2007-02-09 13:06:19
·
answer #2
·
answered by santmann2002 7
·
0⤊
1⤋
10x = 9x + 3
10x - 9x = 3
x = 3
2007-02-09 13:59:23
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
10x-3=9x
take 9x to the left sid and -3 to the right side then u get
10x-9x=3...when u move to the right or left side of any equation the sign changes
therefore x=3
2007-02-09 13:56:22
·
answer #4
·
answered by Musteni s 1
·
0⤊
0⤋
10x-9x=3
x=3
2007-02-09 13:24:27
·
answer #5
·
answered by maidmaz 3
·
0⤊
0⤋
10x - 3 = 9x
10x - 3 - 9x = 9x - 9x
x - 3 = 0
x - 3 + 3 = 0 + 3
x = 3
- - - - - - - -s-
2007-02-09 13:45:12
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
10x - 9x = 3
hence x = 3
Listen i told u know but pleaz try to do these on your own, maybe looking at maths books etc to knw how it is done, asking others online will not help u gain knowledge, u might find my words harsh, but beleive me, im just trying to help u
2007-02-09 13:06:31
·
answer #7
·
answered by wacko 3
·
0⤊
0⤋
fine thanks, and you?
well,
10x-3=9x =>
10x-9x=3 =>
1x=3 =>
x=3!
ok!
i hope i help you!
bye!
2007-02-09 13:08:17
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
simple
first add -9x both side
x - 3 = 0
now add 3 both side
x = 3
2007-02-09 13:05:47
·
answer #9
·
answered by san 3
·
1⤊
0⤋
get all the x's on one side of the =. If you know how to do that it should become obvious quickly.
2007-02-09 13:05:55
·
answer #10
·
answered by LabGrrl 7
·
0⤊
1⤋